A g-c3n4@feoh nanotube / graphdiyne nanomesh composite membrane for oil-water separation, a preparation method and application
Patent Information
- Application Number
- CN202410525481.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-29
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-04-29
AI Technical Summary
本发明解决了现有的油水分离材料难以兼顾油水分离膜的高分离效率、高水通量、高机械强度和自清洁性能等的问题,提出了一种成本低廉、合成方法简单的用于油水分离的g-C3N4@FeOOH纳米管/氧化石墨炔纳米网复合膜的制备方法
[0024]本发明通过材料中氧化石墨炔纳米网的纳米孔洞和亲水性g-C3N4@FeOOH纳米管的嵌入,可以增大层间传递通道,并使水分子低阻力的通过分离孔道,提高了膜的通量。
Smart Images

Figure CN118403508B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of environmental functional materials preparation and application technology, and in particular to a g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane for oil-water separation, its preparation method and application. Background Technology
[0002] With the increasing volume of oily wastewater discharge globally, the need for effective wastewater treatment methods is becoming increasingly urgent. In this regard, research on high-performance and high-strength oil-water separation membranes has become a hot topic. Among these, graphyne oxide, with its extremely high affinity for water molecules and excellent film-forming ability, is a membrane material of great interest. Furthermore, the hydration layer formed on the surface of the hydrophilic graphyne oxide membrane can hinder the adsorption of some pollutants, thus exhibiting a certain degree of antifouling capability.
[0003] However, the mass transfer channels in graphdiyne oxide layered membranes are mainly located at the interlayer and edge junctions. This long and tortuous transport path prolongs the transport distance, thus increasing the time water spends through the membrane and resulting in low membrane permeability. Furthermore, contaminants accumulated during the separation process are difficult to remove using conventional cleaning methods, reducing the membrane's lifespan. Therefore, developing a graphdiyne oxide composite membrane with high flux, high efficiency, self-cleaning properties, and excellent mechanical properties is of great significance in addressing this issue. Summary of the Invention
[0004] The purpose of this invention is to provide a g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane for oil-water separation, its preparation method, and its application. This invention solves the problem that existing oil-water separation materials struggle to simultaneously achieve high separation efficiency, high water flux, high mechanical strength, and self-cleaning properties. It proposes a low-cost and simple synthesis method for preparing a g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane for oil-water separation.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] One of the technical solutions of this invention is to provide a method for preparing a g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite film, wherein the composite film is obtained by loading a modification layer on the surface of a substrate film;
[0007] The modified layer is obtained by self-assembly of g-C3N4@FeOOH nanotube composite material and oxidized graphdiyne nanonet powder; the g-C3N4@FeOOH nanotube composite material is obtained by in-situ growth of iron hydroxyaoxide on the surface of g-C3N4 nanotubes.
[0008] More preferably, the preparation method includes the following steps:
[0009] (1) Melamine and cyanuric acid were mixed in water, reacted, and calcined to obtain g-C3N4 nanotube material; the g-C3N4 nanotubes were then reacted with Fe... 3+ Salt and ammonium salt were mixed in an organic solvent and coated to obtain g-C3N4@FeOOH nanotube composite material;
[0010] (2) Prepare a graphdiyne oxide suspension, add a digesting agent, react, and filter to obtain graphdiyne oxide nanoparticle powder.
[0011] (3) The graphdiyne oxide nanomesh powder and the g-C3N4@FeOOH nanotube composite material are mixed in water, poured into a vacuum filter containing a membrane substrate, and dried to obtain the g-C3N4@FeOOH nanotube / graphdiyne oxide nanomesh composite membrane.
[0012] More preferably, in step (1): the reaction temperature is 160-180℃ and the time is 10-30h; the calcination temperature is 500-600℃ and the time is 2h; the coating reaction temperature is 20-30℃ and the time is 6-12h.
[0013] More preferably, in step (2): the digesting agent is aqua regia, the volume ratio of the graphdiyne oxide suspension to aqua regia is 1:10; and the reaction time is 1 hour.
[0014] More preferably, in step (3): the concentration of the graphdiyne oxide nanonet powder in water is 0.5 mg / mL; the concentration of the g-C3N4@FeOOH nanotube composite material in water is 0.1-0.4 mg / mL.
[0015] More preferably, the molar ratio of melamine to cyanuric acid is 1:1; the g-C3N4 nanotubes and Fe... 3+ The ratio of salt to ammonium salt is 0.2-1.2 g: 1-5 mol: 2-10 mol; the Fe 3+ The salt is ferric chloride, ferric sulfate, or ferric nitrate; the ammonium salt is ammonium chloride, ammonium nitrate, or ammonium bicarbonate.
[0016] Preferably, the membrane substrate is a polyvinylidene fluoride membrane, a polytetrafluoroethylene membrane, a polycarbonate membrane, or a polyethersulfone membrane; the mass ratio of the substrate membrane to the modification layer is 1-3:1-6.
[0017] The second technical solution of the present invention provides a g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite film obtained according to the above preparation method.
[0018] The third technical solution of the present invention provides an application of the above-mentioned g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane in the field of oil-water separation.
[0019] The g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane designed in this invention can be used for the separation of oil-water mixtures and / or oil-water emulsions, and can also be used for the separation of oil-water emulsions containing surfactants (e.g., emulsions containing Tween 80). The types of oils separated include, but are not limited to, toluene, dichloroethane, octane, hexadecane, and soybean oil.
[0020] When separating an oil-water mixture, the composite membrane is first moistened with water before separation. The water in the oil-water mixture passes through the composite membrane, while the oil is trapped outside the composite membrane, thereby achieving the purpose of oil-water separation.
[0021] When separating oil-in-water emulsions, the composite membrane of the present invention can break the emulsion, thereby allowing water to pass through the composite membrane while the oil is trapped outside the composite membrane.
[0022] The g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane provided by this invention has the properties of being superhydrophilic and superoleophilic in air (with a contact angle with water and oil close to 0° in air) and superoleophobic underwater (with a contact angle with oil droplets greater than 150° underwater). Specifically, it can be used for oil-water separation of oily wastewater (such as that containing toluene, dichloroethane, octane, hexadecane, and soybean oil), and for the separation of oil-in-water emulsions without surfactants or containing surfactants (such as emulsions containing sodium dodecyl sulfate or Tween 80).
[0023] The beneficial technical effects of the present invention are as follows:
[0024] This invention increases the interlayer transport channels by embedding the nanopores of the graphdiyne oxide nanonet and the hydrophilic g-C3N4@FeOOH nanotubes in the material, and allows water molecules to pass through the separation channels with low resistance, thereby improving the membrane flux.
[0025] This invention embeds g-C3N4@FeOOH nanotubes into a graphdiyne oxide nanomesh, which provides mechanical support and prevents the compression of micropores. This enables the graphdiyne oxide nanomesh oil-water separation membrane structure to maintain good stability during long-term operation and improves the mechanical properties of the composite membrane.
[0026] This invention, through the embedding of g-C3N4@FeOOH nanotubes, enables the composite membrane to possess excellent photo-Fenton self-cleaning ability and also enhances its wettability by increasing the roughness of the composite membrane. Therefore, it can effectively improve the antifouling performance of oil-water separation membranes and reduce the operating cost of oil-water separation membrane materials.
[0027] This invention is prepared by self-assembling graphdiyne oxide nanonets with core-shell g-C3N4@FeOOH nanotubes and then loading them onto the surface of a substrate membrane. The raw materials used are inexpensive and readily available, and the synthesis method is simple and environmentally friendly. The membrane material is flexible and foldable, has high mechanical strength and good stability, is suitable for oil-water mixtures and oil-water emulsions, and can be recycled, thus having great application value and market prospects.
[0028] This invention addresses the problem that existing oil-water separation materials struggle to simultaneously achieve high separation efficiency, high water flux, high mechanical strength, and self-cleaning properties in oil-water separation membranes. It proposes a low-cost and simple synthesis method for preparing a g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane for oil-water separation. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 This is a photograph of the composite membrane prepared in Example 1.
[0031] Figure 2 SEM images of the g-C3N4@FeOOH nanotube composite material and composite film prepared in Example 1. (a) shows the g-C3N4@FeOOH nanotube composite material, and (b) shows the composite film.
[0032] Figure 3 The images show the surface roughness results and bending optical photographs of the composite film prepared in Example 1. (a) shows the surface roughness results, and (b) shows the bending optical photograph.
[0033] Figure 4 The images show the contact angles of the composite membrane prepared in Example 1 with water and oil in air. The left image represents the water contact angle, and the right image represents the oil contact angle.
[0034] Figure 5 The underwater contact angle results are for the composite membrane prepared in Example 1.
[0035] Figure 6 The images show a physical diagram of the oil-water separation experimental apparatus prepared using the composite membrane in Example 1, along with diagrams illustrating the separation results. In these diagrams, a represents the composite membrane in Example 1; b represents the oil-water emulsion; and c represents the filtrate passing through the composite membrane. Figure 6 The left image shows the actual experimental setup, and the right image shows the results of the separation experiment.
[0036] Figure 7 The image shows the oil-water emulsion separation effect of Example 1; where (a) is an optical microscope photograph of oil-in-water emulsion 1; (b) is an optical photograph of oil-in-water emulsion 1 and the filtrate; and (c) is an optical microscope photograph of the filtrate.
[0037] Figure 8 The water flux results are shown for the graphdiyne oxide nanonet prepared in Comparative Example 2 and the composite membrane prepared in Example 1. Graphdiyne oxide represents the graphdiyne oxide nanonet, and g-C3N4@FeOOH / graphdiyne oxide represents the composite membrane.
[0038] Figure 9 The results show the underwater oil contact angle of the composite membrane prepared in Example 1 before and after photo-Fenton self-cleaning.
[0039] Figure 10 The flux and separation efficiency of the composite membrane circulating separation / photo-Fenton oil-water emulsion in Example 1 are shown. Detailed Implementation
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0041] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0042] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.
[0043] The terms “comprising,” “including,” “having,” “containing,” etc., used in this invention are all open-ended terms, meaning that they include but are not limited to.
[0044] Unless otherwise specified, "room temperature" in this invention refers to 20-30°C.
[0045] All raw materials used in the following embodiments and comparative examples of the present invention are commercially available products.
[0046] Example 1
[0047] Preparation of g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite film:
[0048] (1) Preparation of g-C3N4@FeOOH nanotube composite material: Melamine and cyanuric acid were dissolved in deionized water to obtain melamine solution and cyanuric acid solution, respectively. The melamine solution was slowly added dropwise to the cyanuric acid solution to make the mass ratio of melamine to cyanuric acid 1:1 to obtain a white emulsion. While hot, it was transferred to a hydrothermal reactor and hydrothermally reacted at 160℃ for 10h. The precipitate was washed and dried, and then calcined at 500℃ under an inert atmosphere for 2h to obtain g-C3N4 nanotubes.
[0049] 0.2 g of g-C3N4 nanotubes were dispersed in an alcohol solution, and 1 mol of ferric chloride and 2 mol of ammonium chloride were added. The mixture was stirred at room temperature for 6 h. After centrifugation, washing and drying, g-C3N4@FeOOH nanotube composite material was obtained.
[0050] (2) Preparation of graphdiyne oxide nanonet powder: Graphdiyne oxide was uniformly dispersed in water to obtain a graphdiyne oxide suspension with a concentration of 0.5 mg / mL. Then, aqua regia was added to the suspension (the volume ratio of graphdiyne oxide suspension to aqua regia was 1:10). After ultrasonic and stirring treatment for 1 h, the reaction mixture was poured into ice water and cooled to 25 °C. Subsequently, the solid material was collected by filtration and washing to obtain graphdiyne oxide nanonet powder.
[0051] (3) Loading a modification layer on the substrate membrane surface: The graphdiyne oxide nanonet powder was ultrasonically dispersed in water to prepare a uniform dispersion with a concentration of 0.5 mg / mL. The g-C3N4@FeOOH nanotube composite material was added and ultrasonically dispersed for 10 min to obtain a uniform mixed suspension. During the membrane extraction process, the polyvinylidene fluoride membrane was first fixed on the filter formed between two cylindrical glass tubes. Then the mixed suspension was poured into the upper tube for vacuum filtration. After vacuum filtration and drying, the g-C3N4@FeOOH nanotube / graphdiyne oxide nanonet composite membrane was obtained.
[0052] Figure 1 This is a photograph of the composite membrane prepared in Example 1.
[0053] Figure 2 SEM images of the g-C3N4@FeOOH nanotube composite material and composite film prepared in Example 1 are shown. (a) shows the g-C3N4@FeOOH nanotube composite material, and (b) shows the composite film. Figure 2 It can be seen that the g-C3N4@FeOOH nanotubes embedded in the graphyne oxide nanonet prevent the stacking between the layers, increase the interlayer porosity structure, and at the same time play a role in mechanical support.
[0054] Figure 3 The images show the surface roughness results and curved optical photographs of the composite film prepared in Example 1. (a) shows the surface roughness results, and (b) shows the curved optical photograph. Figure 3 As shown in (a), the surface roughness of the composite membrane significantly increases after the addition of g-C3N4@FeOOH nanotubes. Figure 3 As shown in (b), the composite membrane can be bent up to 180 degrees, indicating that it has good mechanical properties.
[0055] Figure 4 Photographs showing the contact angles of the composite membrane prepared in Example 1 with water and oil in air. The left image represents the water contact angle, and the right image represents the oil contact angle. Figure 4 It can be seen that the contact angle between the composite membrane and water and oil in air is 0, indicating that the surface of the composite membrane has hydrophilic and oleophilic properties in air.
[0056] Example 2
[0057] Preparation of g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite film:
[0058] (1) Preparation of g-C3N4@FeOOH nanotube composite material: Melamine and cyanuric acid were dissolved in deionized water to obtain melamine solution and cyanuric acid solution respectively. The melamine solution was slowly added dropwise to the cyanuric acid solution to make the mass ratio of melamine to cyanuric acid 1:1, and a white emulsion was obtained. While hot, it was transferred to a hydrothermal reactor and hydrothermally reacted at 170℃ for 15h. The precipitate was washed and dried, and then calcined at 550℃ under an inert atmosphere for 2h to obtain g-C3N4 nanotubes.
[0059] 0.6 g of g-C3N4 nanotubes were dispersed in an alcohol solution, and 2 mol of ferric sulfate and 4 mol of ammonium bicarbonate were added. The mixture was stirred at room temperature for 10 h. After centrifugation, washing and drying, g-C3N4@FeOOH nanotube composite material was obtained.
[0060] (2) Preparation of graphdiyne oxide nanonet powder: Graphdiyne oxide was uniformly dispersed in water to obtain a graphdiyne oxide suspension with a concentration of 0.5 mg / mL. Then, aqua regia was added to the suspension (the volume ratio of graphdiyne oxide suspension to aqua regia was 1:10). After ultrasonic and stirring treatment for 1 h, the reaction mixture was poured into ice water and cooled to 25 °C. Subsequently, the solid material was collected by filtration and washing to obtain graphdiyne oxide nanonet powder.
[0061] (3) Loading a modification layer on the substrate membrane surface: The graphdiyne oxide nanonet powder was ultrasonically dispersed in water to prepare a uniform dispersion with a concentration of 0.5 mg / mL. The g-C3N4@FeOOH nanotube composite material was added and ultrasonically dispersed for 10 min to obtain a uniform mixed suspension. During the membrane extraction process, the polyvinylidene fluoride membrane was first fixed on the filter formed between two cylindrical glass tubes. Then the mixed suspension was poured into the upper tube for vacuum filtration. After vacuum filtration and drying, the g-C3N4@FeOOH nanotube / graphdiyne oxide nanonet composite membrane was obtained.
[0062] Example 3
[0063] Preparation of g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite film:
[0064] (1) Preparation of g-C3N4@FeOOH nanotube composite material: Melamine and cyanuric acid were dissolved in deionized water to obtain melamine solution and cyanuric acid solution, respectively. The melamine solution was slowly added dropwise to the cyanuric acid solution to make the mass ratio of melamine to cyanuric acid 1:1, and a white emulsion was obtained. While hot, it was transferred to a hydrothermal reactor and hydrothermally reacted at 180℃ for 20h. The precipitate was washed and dried, and then calcined at 550℃ under an inert atmosphere for 2h to obtain g-C3N4 nanotubes.
[0065] 0.9 g of g-C3N4 nanotubes were dispersed in an alcohol solution, and 4 mol of ferric nitrate and 6 mol of ammonium nitrate were added. The mixture was stirred at room temperature for 12 h. After centrifugation, washing and drying, g-C3N4@FeOOH nanotube composite material was obtained.
[0066] (2) Preparation of graphdiyne oxide nanonet powder: Graphdiyne oxide was uniformly dispersed in water to obtain a graphdiyne oxide suspension with a concentration of 0.5 mg / mL. Then, aqua regia was added to the suspension (the volume ratio of graphdiyne oxide suspension to aqua regia was 1:10). After ultrasonic and stirring treatment for 1 h, the reaction mixture was poured into ice water and cooled to 25 °C. Subsequently, the solid material was collected by filtration and washing to obtain graphdiyne oxide nanonet powder.
[0067] (3) Loading a modification layer on the substrate membrane surface: The graphdiyne oxide nanonet powder was ultrasonically dispersed in water to prepare a uniform dispersion with a concentration of 0.5 mg / mL. The g-C3N4@FeOOH nanotube composite material was added and ultrasonically dispersed for 10 min to obtain a uniform mixed suspension. During the membrane extraction process, the polyvinylidene fluoride membrane was first fixed on the filter formed between two cylindrical glass tubes. Then the mixed suspension was poured into the upper tube for vacuum filtration. After vacuum filtration and drying, the g-C3N4@FeOOH nanotube / graphdiyne oxide nanonet composite membrane was obtained.
[0068] Example 4
[0069] Preparation of g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite film:
[0070] (1) Preparation of g-C3N4@FeOOH nanotube composite material: Melamine and cyanuric acid were dissolved in deionized water to obtain melamine solution and cyanuric acid solution, respectively. The melamine solution was slowly added dropwise to the cyanuric acid solution to make the mass ratio of melamine to cyanuric acid 1:1, and a white emulsion was obtained. While hot, it was transferred to a hydrothermal reactor and hydrothermally reacted at 175℃ for 30h. The precipitate was washed and dried, and then calcined at 600℃ under an inert atmosphere for 2h to obtain g-C3N4 nanotubes.
[0071] 1.2 g of g-C3N4 nanotubes were dispersed in an alcohol solution, and 5 mol of ferric chloride and 10 mol of ammonium bicarbonate were added. The mixture was stirred at room temperature for 12 h. After centrifugation, washing and drying, g-C3N4@FeOOH nanotube composite material was obtained.
[0072] (2) Preparation of graphdiyne oxide nanonet powder: Graphdiyne oxide was uniformly dispersed in water to obtain a graphdiyne oxide suspension with a concentration of 0.5 mg / mL. Then, aqua regia was added to the suspension (the volume ratio of graphdiyne oxide suspension to aqua regia was 1:10). After ultrasonic and stirring treatment for 1 h, the reaction mixture was poured into ice water and cooled to 25 °C. Subsequently, the solid material was collected by filtration and washing to obtain graphdiyne oxide nanonet powder.
[0073] (3) Loading a modification layer on the substrate membrane surface: The graphdiyne oxide nanonet powder was ultrasonically dispersed in water to prepare a uniform dispersion with a concentration of 0.5 mg / mL. The g-C3N4@FeOOH nanotube composite material was added and ultrasonically dispersed for 10 min to obtain a uniform mixed suspension. During the membrane extraction process, the polyvinylidene fluoride membrane was first fixed on the filter formed between two cylindrical glass tubes. Then the mixed suspension was poured into the upper tube for vacuum filtration. After vacuum filtration and drying, the g-C3N4@FeOOH nanotube / graphdiyne oxide nanonet composite membrane was obtained.
[0074] Comparative Example 1
[0075] The only difference from Example 1 is that the composite material is g-C3N4@FeOOH nanotubes, not graphdiyne oxide nanonets. Experimental results show that g-C3N4@FeOOH nanotubes alone cannot form a complete and smooth film.
[0076] Comparative Example 2
[0077] The only difference from Example 1 is that the g-C3N4@FeOOH nanotube composite material is not loaded, but only graphdiyne oxide nanonets are loaded.
[0078] Effect verification
[0079] (1) Figure 8 The water flux results are shown for the graphdiyne oxide nanonet prepared in Comparative Example 2 and the composite membrane prepared in Example 1. Here, graphdiyne oxide represents the graphdiyne oxide nanonet, and g-C3N4@FeOOH / graphdiyne oxide represents the composite membrane. Figure 8 The results show that the flux of pure graphdiyne oxide nanomesh is relatively low, but the flux of the composite membrane water after adding g-C3N4@FeOOH nanotubes is significantly improved. This is related to... Figure 2 Consistent with the SEM results, g-C3N4@FeOOH nanotubes embedded in the graphdiyne oxide nanomesh prevented the stacking between layers, increased the interlayer porosity, facilitated the low-resistance passage of water molecules through the separation channels, and improved the membrane flux.
[0080] (2) The composite membrane obtained in Example 1 was placed in water, and the contact angle between the composite membrane and different oils (dichloromethane, toluene, octane, hexadecane, soybean oil, and crude oil) was measured underwater. The test results are as follows: Figure 5 As shown.
[0081] Figure 5 The contact angle results are for the composite membrane prepared in Example 1. Figure 5 It can be seen that the contact angles of the composite membrane in Example 1 with dichloromethane, toluene, octane, hexadecane, soybean oil, and crude oil are all greater than 150°. Experimental results show that the composite membrane obtained by this invention has typical underwater superoleophobic properties.
[0082] (3)Use Figure 6 The experimental setup shown was used to perform an oil-water mixture separation experiment on the composite membrane obtained in Example 1. The composite membrane material ( Figure 6 a) The composite film is fixed between two clamps and placed vertically in the glass tube, with the upper and lower parts connected to the feed glass tube and the lower part to the discharge glass tube, respectively.
[0083] Octane, Tween 80, and water were mixed in a volume ratio of 1:0.02:100 and magnetically stirred for 90 minutes to obtain oil-in-water emulsion 1. Toluene and water were mixed in a volume ratio of 1:100 and magnetically stirred for 90 minutes to obtain oil-in-water emulsion 2. Hexadecane, Tween 80, and water were mixed in a volume ratio of 1:0.02:100 and magnetically stirred for 90 minutes to obtain oil-in-water emulsion 3. Soybean oil, Tween 80, and water were mixed in a volume ratio of 1:0.02:100 and magnetically stirred for 90 minutes to obtain oil-in-water emulsion 4. Dichloroethane, Tween 80, and water were mixed in a volume ratio of 1:0.02:100 and magnetically stirred for 90 minutes to obtain oil-in-water emulsion 5.
[0084] After wetting the membrane material in this experimental apparatus with water, the oil-water mixture is poured onto the membrane material through the upper feed glass tube. After the emulsion breaks down through the membrane material, the water passes through the membrane material and flows down through the lower discharge glass tube, while the oil is blocked at the top, thus achieving the separation of the oil-water mixture. The combinations of oil-water mixture and membrane material types are shown in Table 1. The separation effect of Example 1 is as follows: Figure 7 As shown.
[0085] Table 1
[0086]
[0087] Figure 6 The images show a physical diagram of the oil-water separation experimental apparatus prepared using the composite membrane in Example 1, along with diagrams illustrating the separation results. In these diagrams, a represents the composite membrane in Example 1; b represents the oil-water emulsion; and c represents the filtrate passing through the composite membrane. Figure 6 The left image shows the actual experimental setup, and the right image shows the results of the separation experiment.
[0088] Figure 7 The images show the oil-water emulsion separation effect of Example 1; where (a) is an optical microscope photograph of oil-in-water emulsion 1; (b) is an optical photograph of oil-in-water emulsion 1 and the filtrate; and (c) is an optical microscope photograph of the filtrate. Figure 7 As can be seen, after oil-water separation, the microstructure of octane can no longer be observed in the microscopic photographs of the filtrate.
[0089] Experimental results of this invention show that the g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane for oil-water separation obtained by the method described in this invention has advantages such as fast separation speed and good separation effect. It is suitable for the separation of general oil-water mixtures and oil-water emulsions, and can separate oil-water mixtures and mixed oil-water emulsions containing toluene, dichloroethane, octane, hexadecane, and soybean oil. Moreover, the g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane has extremely low adhesion properties, is easy to clean, can be reused repeatedly, and has a stable oil-water separation effect.
[0090] (4) In order to further prove the photo-Fenton self-cleaning performance of the g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite film, the photo-Fenton self-cleaning performance of the g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite film was tested with soybean oil as an oily contaminant.
[0091] Figure 9 The underwater oil contact angle results for the composite membrane prepared in Example 1 before and after photo-Fenton self-cleaning are shown. Figure 9As shown, the g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane initially exhibited underwater superoleophobicity, with an underwater OCA of 158.6°. However, the underwater OCA of the soybean oil-contaminated g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane was 121.2°. After 20 minutes of photo-Fenton cleaning, the contaminated g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane regained its underwater superoleophobicity, with an underwater OCA of 158.3°. This demonstrates that the g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane possesses a strong and rapid photo-Fenton self-cleaning ability.
[0092] To evaluate the long-term antifouling ability of the g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane, cyclic oil-water separation (10 times) and photo-Fenton catalytic self-cleaning experiments were conducted.
[0093] Figure 10 The flux and separation efficiency of the composite membrane circulating separation / photo-Fenton oil-water emulsion in Example 1 are shown. Figure 10 As shown, even after 10 cycles, the flux of the g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane for separating soybean oil water emulsion can still reach 106 L / h. -1 m -2 bar -1 The separation efficiency is still higher than 99.0%, indicating that the composite membrane has excellent cycle performance.
[0094] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for preparing a g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite film, characterized in that, The composite membrane is obtained by loading a modification layer onto the surface of a base membrane; The modified layer is obtained by self-assembly of g-C3N4@FeOOH nanotube composite material and graphyne oxide nanonet powder; the g-C3N4@FeOOH nanotube composite material is obtained by in-situ growth of iron hydroxyaoxide on the surface of g-C3N4 nanotubes.
2. The preparation method according to claim 1, characterized in that, The preparation method includes the following steps: (1) Melamine and cyanuric acid were mixed in water, reacted, and calcined to obtain g-C3N4 nanotube material; the g-C3N4 nanotubes were then reacted with Fe... 3+ Salt and ammonium salt were mixed in an organic solvent and coated to obtain g-C3N4@FeOOH nanotube composite material; (2) Prepare a graphdiyne oxide suspension, add a digesting agent, react, and filter to obtain graphdiyne oxide nanoparticle powder. (3) The graphdiyne oxide nanomesh powder and the g-C3N4@FeOOH nanotube composite material are mixed in water, poured into a vacuum filter containing a membrane substrate, and dried to obtain the g-C3N4@FeOOH nanotube / graphdiyne oxide nanomesh composite membrane.
3. The preparation method according to claim 2, characterized in that, In step (1): the reaction temperature is 160-180℃ and the time is 10-30h; the calcination temperature is 500-600℃ and the time is 2h; the coating reaction temperature is 20-30℃ and the time is 6-12h.
4. The preparation method according to claim 2, characterized in that, In step (2): the digesting agent is aqua regia, and the volume ratio of the graphdiyne oxide suspension to aqua regia is 1:10; the reaction time is 1 hour.
5. The preparation method according to claim 2, characterized in that, In step (3): the concentration of the graphdiyne oxide nanonet powder in water is 0.5 mg / mL; the concentration of the g-C3N4@FeOOH nanotube composite material in water is 0.1-0.4 mg / mL.
6. The preparation method according to claim 2, characterized in that, The molar ratio of melamine to cyanuric acid is 1:1; the g-C3N4 nanotubes and Fe... 3+ The ratio of salt to ammonium salt is 0.2-1.2 g: 1-5 mol: 2-10 mol; the Fe 3+ The salt is ferric chloride, ferric sulfate, or ferric nitrate; the ammonium salt is ammonium chloride, ammonium nitrate, or ammonium bicarbonate.
7. The preparation method according to claim 1, characterized in that, The base film is a polyvinylidene fluoride film, a polytetrafluoroethylene film, a polycarbonate film, or a polyethersulfone film; the mass ratio of the base film to the modification layer is 1-3:1-6.
8. A g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite film obtained by the preparation method according to any one of claims 1-7.
9. The application of the g-C3N4@FeOOH nanotube / graphyne oxide nanomesh composite membrane according to claim 8 in the field of oil-water separation.
Citation Information
Patent Citations
Preparation method of graphdiyne oxide membrane material for adsorbing and separating uranium
CN114572960A
Self-cleaning separation membrane as well as preparation method and self-cleaning method thereof
CN116550163A